PENGUATAN SIKAP SALING MENGHARGAI ANTAR KELOMPOK BUDAYA MELALUI IMPLEMENTASI KEGIATAN SABTU BUDAYA DI SMA NEGERI 2 GERUNG - Reni Susilayanti; Herlina Widya Sari; Sumitro (STKIP Subang, 2026)
Indonesia is a country with rich cultural diversity, which presents challenges in creating harmony amidst differences. The Cultural Saturday program at SMAN 2 Gerung is a strategic step to preserve local culture and instill the values ​​of multiculturalism. This study aims to examine how the Cultural Saturday program is implemented and its impacts. This research used a qualitative method with a case study approach, involving interviews, observation, and documentation to explore its implementation and impact. The results indicate that this program, which includes arts activities, regional dances, and cilokaq (a traditional dance performance), is able to increase students' understanding of diversity, strengthen nationalism, and foster tolerance. Obstacles such as limited funding and maintaining student enthusiasm were successfully overcome through collaboration between the school, students, and the community. In conclusion, the Cultural Saturday program is effective in developing a young generation that values ​​cultural diversity and is ready to become agents of change in preserving the nation's cultural heritage.